The Role of Women in Community Development after Earthquake, Tsunami, and Liquefaction in Central Sulawesi, Indonesia - Andi Kurniawan; Syamsul Maarif; Catur Susilo Rahardi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
This study aims at identifying how women respond to uncertain situations after a disaster. Women and children are frequently in a vulnerable position due to their domestic roles. The research took place in Central Sulawesi, where the massive earthquake, tsunami, and liquefaction engulfed thousands of lives and dwellings. Despite their limitation, women have become a social catalyst in enhancing optimism among the survivors. The socio-cultural background of Central Sulawesi women is an essential factor in recovering socio-economic conditions after the disaster in Central Sulawesi. Their toughness and high social care have also facilitated extensive social and economic activities, along with women activists in civil society organizations. Several non-governmental organizations under government coordination have provided rehabilitation assistance programs. The research employed qualitative approaches encompassing in-depth interviews, focus group discussions, and field observations. The research indicates that women's greater participation in disaster recovery programs could be essential. Women also brought up people's optimism to bounce back faster from suffering a disaster.